USE OF INDIGENOUSLY MANUFACTURED APD CYCLER IN PAKISTAN: THE BAHRIA TOWN INTERNATIONAL HOSPITAL EXPERIENCE. - Ahmad, Aftab; Rauf, Tehreem; Qayyum, Ahad; Rana, Asim; Rehan, Irtiqa (Pakistan Journal of Kidney Diseases, 2022)
Patients with end stage renal disease have the option of utilizing peritoneal dialysis (PD) as their mode of renal replacement therapy. There are basically 2 types of PD which include chronic ambulatory peritoneal dialysis (CAPD) and automated peritoneal dialysis. APD is the most preferred type of PD utilized globally because of convenience of nighttime therapy but requires a cycler machine. Unfortunately the APD cycler is not available in Pakistan, hence APD utilization in Pakistan is zero. Byonyks Private Limited have recently manufactured an indigenous device for APD in Pakistan. This abstract is the first experience with that device in Pakistan at Bahria Town International Pakistan Lahore after approval from the local institutional research board and ethical committee (IRBEC).